2001
DOI: 10.1177/002076400104700303
|View full text |Cite
|
Sign up to set email alerts
|

Review Article Case Management: an Update

Abstract: The concept of case management has continued to evolve over the past decade. No controlled trial has been published exploring the model of the case manager as a service broker without responsibility for the provision of care. Basic case management principles have frequently been incorporated within routine clinical practice. Published controlled trials of ACT, which were almost exclusively carried out in North America, have shown markedly positive results. However caution is required in extrapolating these fin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 70 publications
0
18
0
1
Order By: Relevance
“…Their primary functions include (1) the assessment of patient need, (2) the development of individual health care plans for patients, (3) the arrangement of service delivery, (4) the monitoring and assessment of services and (5) evaluation and followup. Those case managers typically have large case loads, with a volume of 50 or more patients, and are office based [35]. Due to the low incidence of ALS and DMD, case management should be adopted for patient groups taking into account a range of diseases that have a high need for ATDs such as neurodegeneration with brain iron accumulation.…”
Section: Financing Assistive Technologiesmentioning
confidence: 99%
“…Their primary functions include (1) the assessment of patient need, (2) the development of individual health care plans for patients, (3) the arrangement of service delivery, (4) the monitoring and assessment of services and (5) evaluation and followup. Those case managers typically have large case loads, with a volume of 50 or more patients, and are office based [35]. Due to the low incidence of ALS and DMD, case management should be adopted for patient groups taking into account a range of diseases that have a high need for ATDs such as neurodegeneration with brain iron accumulation.…”
Section: Financing Assistive Technologiesmentioning
confidence: 99%
“…In regard to the hospitalization rate, the studies conducted in western countries showed that case-management services may increase the hospitalization rate (OR = 1.84) (Holloway and Carson 2001;Marshall and Lockwood 1998) but was effective in three domains of family burden, family satisfaction with services, and cost of care and other clinical features (Laura and Gary 1993;Stephen et al 2000).…”
Section: The Feasibilitymentioning
confidence: 99%
“…For example, the use of a comprehensive and integrated case management program for patients with dual disorders has been associated with patient retention in treatment, improved substance use outcomes, and an increase in the number of days in stable community residences (Drake et al, 1998). Studies of the use of case management for patients with severe mental illness have demonstrated that, within defined settings, specific types of case management services, such as assertive community treatment (ACT), result in improved follow-up and an increase in service utilization, along with a decrease in inpatient hospital admissions and inpatient bed days (Holloway & Carson, 2001). Other studies, however, have reported that the use of case management with the severely mentally ill does not necessarily Case management services are considered by many to be important but expensive.…”
Section: Costs and Outcomes Of Case Managementmentioning
confidence: 99%
“…In order for case management to be effective, services must be available and consumed. Clients who are offered case management services are more likely to follow up with services, which may increase service utilization but may not necessarily improve clinical outcomes (Holloway & Carson, 2001). From a cost-containment perspective, the relationship between utilization of services and outcomes is less clear.…”
Section: Utilization Of Case Managementmentioning
confidence: 99%